2020
DOI: 10.3390/en13133426
|View full text |Cite
|
Sign up to set email alerts
|

Financial Liberalisation, Political Stability, and Economic Determinants of Real Economic Growth in Kenya

Abstract: This study aimed to analyse financial liberalisation, political stability, and economic determinants of Kenya’s real economic growth using time series data over the period of 1970–2016. The authors specified quadratic and interactive models to be estimated by employing a quantile regression analysis. The traditional and quantile unit root test was used in testing the stationarity issue. The co-integration findings indicated that the capital account openness and financial development impede on real econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
8
12
0
Order By: Relevance
“…On the other hand, it takes a long term for the level of nancial development to aid economic prosperity. This outcome supports empirical submission by Ali and Sardar (2020) and Yakubu et al (2020). Sustained credit facilities to the private sector reduce unemployment of factor inputs.…”
Section: Dynamic Ardl Simulationssupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, it takes a long term for the level of nancial development to aid economic prosperity. This outcome supports empirical submission by Ali and Sardar (2020) and Yakubu et al (2020). Sustained credit facilities to the private sector reduce unemployment of factor inputs.…”
Section: Dynamic Ardl Simulationssupporting
confidence: 79%
“…Table 9 further shows that de cit nancing exacted a signi cant negative effect on economic prosperity in the short and long term. and Yakubu et al (2020) are two studies to have reported similar ndings in the literature. This outcome implies that the supplementary funds derived through de cit nancing to augment the use of revenue for infrastructural development have been incomediminishing.…”
Section: Dynamic Ardl Simulationssupporting
confidence: 66%
“…The financial development was proxied by domestic credit as a portion of GDP in this study, too. Chandio et al [35], in the case of Pakistan, and Yakubu et al [36], in the case of Kenya, used this variable as an indicator for financial development. The proxy of economic growth (GDP) is real GDP per capita (2010 USD).…”
Section: Functional Specification and Datamentioning
confidence: 99%
“…The coefficients of export diversification in regression models ( 1) and ( 2) propose that a percentage upsurge in the export diversification index of a country in SADC will reason more growth about 1 percent and The correlation between political stability and economic growth is indisputable. Economic growth in a country depends on the development strategies created and implemented by its political system (Corovei & Socol, 2019;Yakubu et al, 2020). A country's political system is accurate in determining its fate.…”
Section: Resultsmentioning
confidence: 99%